HUBUNGAN ANTARA KOMITE AUDIT DENGAN KETEPATAN WAKTU PELAPORAN KEUANGAN: KUALITAS AUDITOR SEBAGAI VARIABEL INTERVENING - Galih Satria Dirgantara; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
This study to analyze the influence of the audit committee to the timeliness of financial reporting with the quality auditors as varabel intervening. This study makes the quality of the auditor as an intervening variable because of the relationship of the audit committee as a body established by the board of directors in a company whose job is to choose the external auditors where external auditors are good is the auditor who has qualities that will tend to more quickly complete the audit assignment they receive so that financial reporting can be achieved in a timely manner.The samples used are 297 companies listed on the Stock Exchange in 2010-2012. The results of this study identified that the audit committee has an influence on the quality of auditors and the quality of the auditor has an influence on the timeliness of financial reporting.